Determinants of Educated Unemployment in WestJawa Province in 2017-2021 - Aziza Retnamning Bahira; Winny Perwithosuc; Anisa Riski Apriani (IECON: International Economics and Business Conference, 2023)
Educated unemployment is a problem that often occurs in Indonesia, especially in the West Java Province, because economic growth and wages are quite high. Economic growth and high wages not offset by employment will increase the number of educated unemployed. This study aims to determine the determinants of educated unemployment in regencies/cities in West Java Province. This study used secondary data from combined panel data between cross sections covering 27 regencies/cities in West Java Province and timeseries for five years from 2017 to 2021. The approach method used in estimating this panel data is the Fixed Effect Model (FEM). The results of the regression of this panel data show that the minimum wage has a positive and significant effect on educated unemployment, the GRDP has a positive and significant effect on educated unemployment, the human development index hasa negative and significant effect on educated unemployment. In contrast, the population number variable has a negative and insignificant effect on educated unemployment.